Indonesian EFL students’ narratives of corrective feedback in speaking instruction - Anita Anita; Abdul Gafur Marzuki; Huriyah Huriyah; Nuraeni Nuraeni; Dhiza Yulia Sangkarini; Ana Kuliahana (Universitas Islam Negeri Ar-Raniry, 2026)
Corrective feedback constitutes a critical component in the development of speaking proficiency within English as a foreign language (EFL) contexts. Nevertheless, learners' subjective experiences of such feedback remain underexplored, particularly within the landscape of Indonesian higher education. This study investigates Indonesian EFL students’ narratives concerning the corrective feedback they receive in speaking classes and examines how such feedback shapes their speaking development. Employing a qualitative narrative inquiry design, data were collected through semi-structured interviews with eight fourth-semester students from the English Education Department at UIN Sultan Maulana Hasanuddin Banten. The findings indicate that direct corrective feedback is perceived as the most impactful type, particularly for improving pronunciation, lexical range, fluency, and speaking confidence, owing to its immediacy and clarity. Indirect feedback, primarily delivered in written form, was found to facilitate grammatical reflection and reduce learner anxiety, although its effectiveness was contingent upon subsequent reinforcement. Peer feedback emerged as the most emotionally comfortable and collaborative modality, fostering learner engagement, autonomy, and willingness to communicate, especially in informal and technology-mediated settings. Collectively, the results suggest that effective speaking instruction necessitates the flexible integration of direct, indirect, and peer feedback strategies that are responsive to learners’ linguistic needs and affective dimensions. By foregrounding students’ narrative accounts, this research contributes to a more nuanced understanding of corrective feedback practices in Indonesian EFL speaking classrooms and offers pedagogical insights to support more learner-centered feedback design.